Finos Fios, Renda de Agulha... Uma Alternativa de Trabalho, Múltiplos Olhares para a Qualidade - Rogério Zanon da Silveira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
This article emphasizes the work done by the renters of Divina Pastora, a municipality located in the eastern Sergipano mesoregion, in the Cotinguiba microregion, a tourist region called ‘Polo dos Tabuleiros’, with an emphasis on the Irish income produced by Ecotourism. The objective of this research is to evaluate the satisfaction of Irish Income buyers in relation to the quality of services provided by artisans who market and produce embroidery - a central cultural element of local identity. The methodology of this study is descriptive, quantitative and qualitative and adaptive of the metric-methodological approach Servqual. The results obtained suggest that the quality attributes are delineated primarily by the tangible and empathic constructs. At the end, commercial, academic and socio-cultural implications are discussed, encompassing the context of Cultural Heritage and the art of know-how of women artisans in the region surveyed.